Factors Associated with Acceptance of Tuberculosis Preventive Therapy Among Household Contacts in Lhokseumawe - Hendra Wahyuni; Rizka Sofia; Anugrah A Warid Rambe (Fakultas Kedokteran Universitas Malikussaleh, 2026)
Household contacts of tuberculosis (TB) patients are among the groups at highest risk of contracting TB, a condition preventable through Tuberculosis Preventive Therapy (TPT). This study aimed to identify factors associated with TPT acceptance among household contacts of pulmonary TB patients at public health centers in Lhokseumawe City. An analytical observational study with a cross-sectional design was conducted involving 139 household contacts of pulmonary TB patients. Subjects were recruited based on predefined inclusion and exclusion criteria. Data were collected using a structured questionnaire and analyzed using Fisher's exact test at a significance level of 0.05. The history of tuberculin skin test (TST) examination was the only variable significantly associated with TPT acceptance (p = 0.048). No significant associations were found for age, sex, education level, relationship to the TB patient, knowledge level, distance from health center, or receipt of TPT education. A total of 137 of 139 respondents (98.6%) refused TPT, reflecting a critically low acceptance rate that demands programmatic attention. Intensification of TST-integrated contact investigation and more targeted counseling approaches are recommended to improve TPT uptake.